Translation of the chronicle "Nhemonguetá" - Drummond de Andrade, Carlos; DePaula, Lillian (Tusaaji: A Translation Review, 2015)
Translation from Portuguese into English of the chronicle "Nhemonguetá" by Carlos Dummond de Andrade.